Analysis of Flood Discharge at the Top of the Brukah River Due to Changes in Land Use of the Sindu Kalibening Block in Banjarnegara - Kuncoro, Ahmad Hakim Bintang; Susilowati, Susilowati (Teknika, 2024)
The Sindu Block area in Kalibening District, Banjarnegara Regency, is a rice field area 1000 meters above sea level that often floods during the rainy season. The initial indications of the cause of flooding are high rainfall, siltation of rivers, and changes in forest land use. There is a need for research related to land use change in the Kalibening area to determine its effect on the peak discharge of the Brukah River flood. The purpose of this study is to determine the effect of land use change on the percentage of increase in peak flood discharge in the Brukah River. The calculation of peak flood discharge in this study uses the HEC-HMS application with GPM satellite rainfall data, frequency analysis using Hydrognomon, and baseflow using the Gama 1 equation. The simulation results showed that the comparison between ideal conditions and other conditions in percentage terms from Q2th, Q5th, Q10th, Q25th, and Q50th was an average of 14.1% - 10.7% for 2012 conditions, then 15.7% - 11.7% for 2020 conditions, and 22.7% - 16.1% for severe conditions. Land use changes significantly affect peak flood discharge, especially in the Brukah River in the Sindu Kalibening Block area of Banjarnegara.
Keywords: Flood; Gama 1; GPM; Hydrognomon; Landuse